Ex Vivo Enteroids Recapitulate In Vivo Citrulline Production in Mice - Wang, Xiaoying (J Nutr, 2018)
BACKGROUND: The endogenous production of arginine relies on the synthesis of citrulline by enteral ornithine transcarbamylase (OTC). Mutations in the gene coding for this enzyme are the most frequent cause of urea cycle disorders. There is a lack of correlation between in vivo metabolic function and DNA sequence, transcript abundance, or in vitro enzyme activity. OBJECTIVE: The goal of the present work was to test the hypothesis that enteroids, a novel ex vivo model, are able to recapitulate the in vivo citrulline production of wild-type (WT) and mutant mice. METHODS: Six-week-old male WT and OTC-deficient mice [sparse fur and abnormal skin (spf-ash) mutation] were studied. Urea and citrulline fluxes were determined in vivo, and OTC abundance was measured in liver and gut tissue. Intestinal crypts were isolated and cultured to develop enteroids. Ex vivo citrulline production and OTC abundance were determined in these enteroids. RESULTS: Liver OTC abundance was lower (mean ± SE: 0.16 ± 0.01 compared with 1.85 ± 0.18 arbitrary units; P < 0.001) in spf-ash mice than in WT mice, but there was no difference in urea production. In gut tissue, OTC was barely detectable in mutant mice; despite this, a lower but substantial citrulline production (67 ± 3 compared with 167 ± 8 µmol · kg(−1) · h(−1); P < 0.001) was shown in the mutant mice. Enteroids recapitulated the in vivo findings of a very low OTC content accompanied by a reduced citrulline production (1.07 ± 0.20 compared with 4.64 ± 0.44 nmol · µg DNA(−1) · d(−1); P < 0.001). CONCLUSIONS: Enteroids recapitulate in vivo citrulline production and offer the opportunity to study the regulation of citrulline production in a highly manipulable system.